The Relationship Between Oral Antidiabetic Treatment And Blood Sugar Level Among Type 2 Diabetes Mellitus Patients in Nur Hidayah Hospital Yogyakarta. - Pujilestari, Mardiana; Titami, Arina; Sugiyono, Sugiyono (Universitas Ahmad Dahlan, 2025)
Background: Diabetes mellitus is a chronic disease that poses a global health threat, with type 2 diabetes mellitus accounts for 90% of all cases. In Indonesia, diabetes mellitus is among the causes of high mortality due to non-communicable diseases. If not treated properly, type 2 diabetes mellitus can lead to various complications, potentially worsening the patient's condition. To address this, blood glucose levels must be controlled through the use of oral antidiabetic medications, either as monotherapy or in combination therapy. This study aims to the accuracy of oral antidiabetic drugs use and its therapy outcomes (blood sugar levels) in type 2 diabetes mellitus patients at Nur Hidayah Hospital Yogyakarta. Method: This study is an observational study with retrospective data collection, carried out using the purposive sampling method. A total of 75 samples were obtained from 298 populations that met the specified criteria. Univariate data analysis methods are presented in the form of percentages and tables, including analyses of patient characteristics, treatment characteristics, and therapy outcomes. Subsequently, bivariate analysis was conducted using the chi-square test to determine the relationship between the accuracy of oral antidiabetic drugs use and therapy outcomes, specifically blood sugar levels of patients with type 2 diabetes mellitus. Results: The findings of the analysis performed using the chi-square test revealed a correlation between the accuracy of oral antidiabetic medication and blood sugar levels in patients (p-value=0.012). Conclusion: proper use of oral antidiabetics shows that the patient's blood sugar levels are controlled.